VIDEO FORENSIK SEBAGAI ALAT BUKTI PETUNJUK PADA TINDAK PIDANA PEMBUNUHAN - Salma Elsa Tiziana (2022)
Video forensic is a part of digital forensics which can be defined as forensics in the form of video recordings which usually come from cameras and CCTV (Close Circuit Television). In the applicable procedural law in Indonesia, cameras and CCTV are included in electronic evidence. Electronic evidence is used to investigate and establish facts at trial, but the existence of electronic evidence is not regulated in Article 184 paragraph (1) of the Criminal Procedure Code (KUHAP). The research method used is normative juridical with a statutory approach, a case approach and a conceptual approach. The results of the study show that the strength of evidence from electronic evidence is strong even though electronic evidence is not regulated in the Criminal Procedure Code, but the regulation is in Article 5 of the ITE Law, therefore, to achieve material truth, electronic evidence can also be used as legal evidence and included in the indication. The existence of electronic evidence is proven to be able to assist in uncovering various criminal acts. So that the use of electronic evidence is increasingly being proposed in various court cases as an effort to prove and assist in solving various criminal cases, and as a judge's consideration in giving their decisions. However, a criminal law policy is needed that clearly regulates electronic evidence and this has been regulated in Article 175 paragraph (1) of the Draft of Criminal Procedure Code, namely there is an expansion of evidence with electronic evidence as legal evidence. So it is hoped that the Draft of Criminal Procedure Code will soon be ratified in order to realize the legal objectives of justice, certainty and expediency.